Longitudinal covariance of resting-state cardiac function and borderline personality disorder symptoms in adolescent non-suicidal self-injury - Koenig, Julian; Weise, Sindy; Gaber, Lena; Parzer, Peter; Resch, Franz; Kaess, Michael (The world journal of biological psychiatry, 2018)
Objectives: Cardiac function is altered in borderline personality disorder (BPD). In adolescents with non-suicidal self-injury (NSSI) resting heart rate (HR) and vagally mediated heart rate variability (vmHRV) are associated with BPD symptoms. The study aimed to investigate longitudinal covariance of BPD symptoms and cardiac function in adolescent NSSI.Methods: HR and vmHRV were recorded in female adolescents with NSSI (n = 17) completing a baseline and 1-year follow-up assessment. Physiological data, structured clinical interviews and self-reports were obtained at both time points. Predictors of change in clinical outcomes and cardiac function were assessed.Results: Patients showed a reduction of NSSI (z(34;17) = -3.79, P < 0.0001), depressive symptoms (z(34;17) = -3.74, P < 0.0001), and increases in the level of functioning (z(34;17) = 2.87, P = 0.004). Symptoms of BPD and frequency of BPD diagnosis did not significantly change. No significant differences on HR or vmHRV were observed. Changes in BPD symptoms were associated with changes in HR (r(17)= 0.532, P = 0.028) and vmHRV (r(17) = -0.516, P = 0.033).Conclusions: Longitudinal changes in BPD symptomatology in adolescents engaging in NSSI are associated with changes in resting cardiac function. Clinical studies are needed to investigate the utility of cardiac markers to track treatment outcome in adolescents with BPD.
Published online: 29 Jun 2017
Gesehen am 24.10.2018